Motivación de logro académico y rendimiento académico en alumnos de secundaria de una institución educativa del Callao - Yactayo Cornejo, Yoel Leo (2010)
The intention of this investigation is to establish the relation between the motivation of achievement and the academic performance in pupils of secondary. I apply to him a test of Motivation of academic achievement (MLA) in pupils of secondary. The sample belonged 93 pupils of third party, fourth and fifthly of secondary in the mixed I.E. Fe y Alegría 43 of Ventanilla Callao with ages between 14 and 18 years. There was obtained an index of correlation of 0.39 by means of Sperman's test. One found relation moderated between the motivation of achievement and the academic performance, also that the women have a motivation of achievement bigger than the males.